Folliculotropic mycosis fungoides: clinicopathological analysis of 17 patients. (18th November 2014) - Marschalkó, M.; Erős, N.; Kontár, O.; Hidvégi, B.; Telek, J.; Hársing, J.; Jókai, H.; Bottlik, G.; Rajnai, H.; Szepesi, Á.; Matolcsy, A.; Kárpáti, S.; et al.
Abstract: Background: Folliculotropic mycosis fungoides (FMF) represents a variant of MF characterized by hair follicle invasion of mature, CD4‐positive small lymphoid cells with cerebriform nuclei. The disease displays resistance to standard treatment modalities and has an unfavourable course. Objective: Clinical analysis of 17 patients with FMF collected between 2005 and 2012, investigation of tumour cells and involved hair follicle. Methods: Re‐evaluation of clinical data, wide panel immunohistochemistry investigation on paraffin‐embedded biopsy material, T‐cell receptor gene rearrangement analysis of the samples. Results: Male and older age group predominance, frequent head–neck involvement, acneiform lesions, keratotic plugs, cysts, nodules, follicular papules, alopecia and classic mycosis fungoides‐like plaques represented the main clinical characteristics. Treatment response showed a wide range from transient complete response to therapy resistance and death due to the disease. The pathological alterations: folliculotropism, mild epidermotropism, follicular plugging, mucinous degeneration of hair follicle, basaloid hyperplasia, syringotropism were similar to those observed previously. The first case of a CD8‐positive folliculotropic mycosis fungoides – with unusual clinical presentation – is reported here. Nestin overexpression of mesenchymal cells of the isthmic and suprabulbar regions of hair follicle and the reappearance of dermal nestin‐expressing cells were observed in association with immature dendritic cell hyperplasia. Altered CK19 expression was detected suggesting a potential role of follicular keratinocytes in the disease process. It was found that a proportion of neoplastic T cells constantly express programmed death‐1 receptor in our patients contrary to classic mycosis fungoides. Conclusion: The spectrum of the clinical manifestation and the course of folliculotropic mycosis fungoides are broad and differ from classic mycosis fungoides. Folliculotropic neoplastic T‐cell proliferation is associated with activation of inflammatory reactive T‐ and B‐lymphoid cells, mesenchymal cells and changes in the hair follicle.